O papel da biblioteca no processo educativo do aluno de engenharia e o ciclo de comunicação interna na transferência de informação - Jensen, Leo Roberto (1991)
Study on the degree of library participation at the library located in the School of Universidade Federal Fluminense, considering the learning processs experienced by the Engineering student in the subjects offered by theTechnical Drawing Department and the communication flow among students, teachers and librarians, viewed as a stimulating factor in library use. The data was collected though a questionaire, and the analysis presented as basis the particulars of technological informtion, the adjustment of the library's material and services to the specific needs and demands of the Department, and computer advantages, both to library activities and to teacher's didactical support. The discussion also focuses on the friction points within the internal communication cycle and its interference in library use. The conclusions set off the need for a restructuring of the roles of the library, the librarians and the teachers, so that all of them accomplis their goals. To achieve such goals, some recommendations are the implementation of regular user training, and the inclusion of the subect "Introduction To Library Techniques" in the curriculum.